1993
DOI: 10.1002/1097-4679(199305)49:3<385::aid-jclp2270490313>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function in borderline personality disorder

Abstract: To evaluate the possibility of an underlying dimension of organicity in borderline personality disorder (BPD), a carefully diagnosed group of borderline patients was assessed across a wide range of neuropsychological functions and then was compared to an age-and education-matched nonpatient control group. The BPD group had significantly lower Verbal, Performance, and Full Scale IQ scores on the WAIS-R. The BPD group also was impaired significantly on motor skills, figural memory, complex visuomotor integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 34 publications
2
45
2
8
Order By: Relevance
“…Additionally, the cognitive functioning of patients with BPD was not impaired by emotional stimuli. These results failed to replicate previous findings with regard to the Stroop (Carpenter et al, 1993;Swirsky-Sacchetti et al, 1993) or Trails B (Carpenter et al, 1993;van Reekum et al, 1993) The one expected finding was that depressed patients demonstrated psychomotor slowing compared to the other groups (although only one of the differences was significant using covariates) and generally poorer performance on story recall. However, the performance of depressives was not impacted by emotional stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, the cognitive functioning of patients with BPD was not impaired by emotional stimuli. These results failed to replicate previous findings with regard to the Stroop (Carpenter et al, 1993;Swirsky-Sacchetti et al, 1993) or Trails B (Carpenter et al, 1993;van Reekum et al, 1993) The one expected finding was that depressed patients demonstrated psychomotor slowing compared to the other groups (although only one of the differences was significant using covariates) and generally poorer performance on story recall. However, the performance of depressives was not impacted by emotional stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…Order of lists and interference conditions were counterbalanced to control for learning effects. The neutral interference consisted of serial sevens (i.e., counting backwards from 100 by 7) while the emotional interference required subjects to tell a story about Thematic Apperception Card #13 MF, which often evokes stories about rape or murder (Swirsky-Sacchetti et al, 1993).…”
Section: Story Recall Taskmentioning
confidence: 95%
See 2 more Smart Citations
“…Swirsky-Sacchetti et al (1993) obtiennent par ailleurs des résultats qui montrent une susceptibilité accrue à l'interférence en plus d'atteintes aux habiletés motrices, une pauvre mémoire non verbale et une difficulté d'intégration visuomotrice complexe chez les patients avec un TPL. Bazanis et al (2002) ont observé des atteintes significatives lors de tests exécutifs qui impliquent la prise de décision et la planification.…”
Section: Survol De La Recherche Sur Les Fonctions Exécutives Des Persunclassified